KLITIKA DALAM KLAUSA PASIF BAHASA MANGGARAI - Stephanus Mangga (Linguistik Indonesia, 2016)
This study is about clitics in passive clauses in Manggarai, a language in West Flores. The purpose of this study is to describe the type, location, and function of the clitics that occur in the passive clauses of the language. The data were collected by using introspection technique and, following Mahsun (2013), were analyzed by using position interchange technique of constituents in the passive clauses in order to determine the structure of information and to find the change of syntactic function of the clitics in the clause. The result of this study reveals two things:  a) an enclitic of subject pronoun attached to phrase agents and verbs is a pronominal copy of the subject patient, and b) an enclitic of a genitive pronoun serves as a possession marker and nominalization marker.